2005
DOI: 10.1111/j.0014-3820.2005.tb01774.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Environmental Component of the Phenotypic Variance: Stabilizing Selection in Changing Environments and the Cost of Homogeneity

Abstract: Quantitative traits show abundant genetic, environmental, and phenotypic variance, yet if they are subject to stabilizing selection for an optimal phenotype, both the genetic and environmental components are expected to decline. The mechanisms that determine the level and maintenance of phenotypic variance are not yet fully understood. While there has been extensive study of mechanisms maintaining genetic variability, it has generally been assumed that environmental variance is not dependent on the genotype an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 42 publications
2
77
0
1
Order By: Relevance
“…Methodology: Comparison of genetic models: Different genetic models to account for genetic heterogeneity of environmental variance appear in the literature, basically either additive effects both at the level of the mean and at the level of the environmental variance Zhang and Hill 2005; this study) or additive effects on the mean and an exponential model for the environmental variance (SanCristobal-Gaudy et al 1998Sorensen and Waagepetersen 2003;Ros et al 2004). In the exponential model…”
Section: Discussionmentioning
confidence: 99%
“…Methodology: Comparison of genetic models: Different genetic models to account for genetic heterogeneity of environmental variance appear in the literature, basically either additive effects both at the level of the mean and at the level of the environmental variance Zhang and Hill 2005; this study) or additive effects on the mean and an exponential model for the environmental variance (SanCristobal-Gaudy et al 1998Sorensen and Waagepetersen 2003;Ros et al 2004). In the exponential model…”
Section: Discussionmentioning
confidence: 99%
“…However, Ibáñez-Escriche et al [20] found no correlation for slaughter weight at 175 days in pigs while Gutiérrez et al [14] found extreme positive and negative correlations depending on the trait, and Damgaard et al [4] and Huby et al [17] found positive genetic correlations between mean and variability for weight in pigs. Moreover, Zhang et al [36] found in the literature a wide range of values for correlations between mean and variability. The negative correlation between mean and environmental variance (−0.19) for WG, means that we should expect the environmental variance for this trait to decrease in an experiment conducted to increase the mean of the trait.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that before implementing such a selection index, further studies are required to understand the functional relationship between mean and variance and their influence on the expected correlated response. Thus, it would be desirable to explore other models [36] with different relationships between mean and variance. Another possibility would be to validate the models by comparing their expected response to selection with a selection experiment for variability.…”
Section: Discussionmentioning
confidence: 99%
“…The clonal frequency change due to mutation and selection follows equation (14). As in Zhang and Hill (2005b), the squared mean phenotype 2 is used as a unit to measure the variance, and thus the average values are V E ϭ 0.005 2 , 2 ϭ 0.1 2 , and ϭ 2V M / ഠ (10 Ϫ5 /) 2 (V M is the mutational variance, of 2 the order of 10 Ϫ3 of the environmental variance (Lynch and Walsh 1998)). Because no direct knowledge of the relevant parameter of slope is available, values of the intrinsic mean m and variance of slope will be assigned arbitrarily.…”
Section: And W Ilt Is Given By Equation (2)mentioning
confidence: 99%
“…Accumulating evidence suggests that environmental variance is under genetic control (Whitlock and Fowler 1999;Sorensen and Waagepetersen 2003;Ros et al 2004;Rowe et al 2005;Mackay and Lyman 2005). Although much theoretical attention has been paid to the maintenance of genetic variation (Bü rger 2000; Barton and Keightley 2002;Zhang and Hill 2005a), and a little to environmental variance within quantitative traits (Bull 1987;Zhang and Hill 2005b), no comprehensive model has been described for both variances together. However, genetic models that ignore gene-environment interactions do not explain the robust patterns of genetic and environmental variances.…”
mentioning
confidence: 99%